'Old habits die hard':* discourses of urban filth in Swachh Bharat Mission and The Ugly Indian. Issue 2 (3rd April 2018) - Luthra, Aman
ABSTRACT: Popular framings of the contemporary urban Indian waste crisis focus on the crucial need for public behavior change. This article provides an exploratory study of the ideology and work of two social media campaigns – Swachh Bharat (Clean India) Mission and The Ugly Indian, a social media group – which emphasize the need for inculcating 'modern' civic behaviors of not littering, and volunteering to clean up public spaces, and examines the following questions: What types of urban imaginaries are invoked in the discussions of urban filth? Do these discussions betray structural (class-based) biases in the aesthetic ideologies they imagine and invoke? Do these discussions reify the public-private dichotomy that has puzzled scholars concerned with hygiene in urban India? Discourses deployed in these campaigns reproduce colonial and post-colonial narratives of hygiene as a 'cultural problem' premised on an idea of a pre-modern urban subject who needs to be disciplined. By focusing on behavior change, these campaigns privilege an understanding of waste as an aesthetic problem rather than as a much more complicated infrastructural one. As these campaigns focus on highlighting and celebrating the volunteer labor of the privileged, they may also obfuscate the economically necessary labors of the marginalized.